Sympathetic Skin Response in Young Patients with ALS - Hasan, Mehedi; SK. Mahbub Alam,; Hasan Zahidur Rahman,; Abdullah Al Muzahid,; Maftahul Jannat,; Sujan Saha,; Md. Shofikul Islam,; Ashish Chowdhury, (Bangladesh Journal of Neuroscience, 2026)
Background: Motor neuron disease (MND) is now considered as the third most common neurodegenerative disorder. Among several types of MND, amyotrophic lateral sclerosis (ALS) is the most common and relentlessly progressive incurable disorder. Many hypotheses have been put forward to see autonomic involvement in ALS. Previous studies have found an association between sympathetic skin response (SSR) and ALS as a part of autonomic involvement. SSR may be absent or increased in latency or decreased in amplitude in ALS which are associated with severity of illness. Objective: The objective of this study was to see the association of SSR in young patients with ALS. Materials and Methods: This case control study was carried out in the Department of neurology, BSMMU, Dhaka, from April 2018 to September 2019. Total 38 subjects of less than 40-years-age were enrolled as study population after satisfying inclusion and exclusion criteria. Among them, 19 were grouped as case and rest 19 were control. All patients with ALS were diagnosed according to The Revised El Escorial diagnostic criteria fulfilling definite, probable, probable lab-supported and possible cases of ALS with no family history ofALS. The SSR was recorded on NIHON KOHDEN Neuropack MEB-9400 S1 Series EMG/NCV/EP Measuring System in the department of Neurology, BSMMU. Results: The mean age of the cases was 25.68 ± 7.71 years all of whom were male. The mean disease duration was 17.9±7.8 months at the time of examination; and 15(78.9%) had mild disease and 4(21.1%) had moderate severity of disease. We observed mean onset latency in cases to be 1521.2±230.2ms in upper limb and 2551.0±404.0ms in lower limb; which were significantly longer than control group (p value <0.001). We also noticed mean SSR amplitude to be 1.01±0.88mV in upper limbs and 0.59±0.53mV in lower limbs which were significantly lower than control group (p value <0.001). In upper limb, among 19 cases, SSR was absent in 2 (10.5%) and increased latency in 6(31.6%) which was significantly different than control (p=0.006). In lower limbs, SSR was absent in 9 (47.4%) cases and increased latency in 9(47.4%) cases which also was significantly (<0.001) different than control group. Conclusion: The present study revealed significant association of sympathetic skin response abnormality in young patients with ALS.